Multidrug-resistant Pseudomonas aeruginosa isolate co-expressing extended-spectrum ?-lactamase PER-1 and metallo-?-lactamase VIM-2 from Turkey - Yakupogullari, Yusuf; Poirel, Laurent; Bernabeu, Sandrine; Kizirgil, Ahmet; Nordmann, Patrice (Oxford Univ Press, 2008)
[Abstract Not Available]
Keywords: P. aeruginosa; ESBLs; MBLs